NEOMODERN AS OPPORTUNITY - I. V. Gibelev (Концепт: философия, религия, культура, 2018)
The article discusses the opportunities of Neomodern philosophical conceptualization as a reflexive and cultural horizon of future. The methodological searching is grounding on ontological transcendental phenomenology conception. The problem of historicity and post-history correlation is used as a material and an object for that searching. In this connection the main question that must be answered in transcendental phenomenology consists, firstly, in philosophical content of Neomodern definition and, secondly, in comprehending opportunities of invariability or evolutionary of post-historic society. Besides that, there is a special place for morality phenomena in the process of transcendental thought renewal in finding a way out of the post-history to the person's history For these purposes the research is focused upon the border concept in Hegel's pure phenomenology and the border concept in ontological transcendental phenomenology. Thus, the post-historical actualization of Reason responsibility principle for the way the border with the other is established is essential. The comparison of two ways of interpretation of the border identifies the cause of the inner discord of Modernity project. It is the absence of such a definition of human subjectivity borders in which the otherness is the determination of freedom in the world of natural phenomena. That's why it is necessary to consider the opportunity of involving the sacral aspect of other into immanence of radically historical living of a human being. Investigation result is the understanding of the task to renew the Hegelian's negativity concept working in a Reason activity structure within its transcendental and existential aspects. In a sphere of a Life World the Reason self-relation and self-validity appears as individual historical self-temporalization. For the Reason the opportunity of its self-going for the future from the post-history appears as a kenotic engagement and the motion of sacred determinations.